2022
DOI: 10.1051/0004-6361/202244150
|View full text |Cite
|
Sign up to set email alerts
|

Theory of solar oscillations in the inertial frequency range: Amplitudes of equatorial modes from a nonlinear rotating convection simulation

Abstract: Context. Several types of inertial modes have been detected on the Sun. Properties of these inertial modes have been studied in the linear regime but have not been studied in nonlinear simulations of solar rotating convection. Comparing the nonlinear simulations, the linear theory, and the solar observations is important to better understand the differences between the models and the real Sun. Aims. We wish to detect and characterize the modes present in a nonlinear numerical simulation of solar convection, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 79 publications
3
30
1
Order By: Relevance
“…We can clearly see the existence of the equatorial Rossby modes as represented by a clear power ridge along the expected dispersion relations (red points) for 3 ≤ m ≤ 12. In our simulation, these Rossby modes are excited both by the non-axisymmetric random fluctuations in the Λ-effect and by the non-axisymmetric Lorentz-force; this is different from the rotating convection simulation of Bekki et al (2022b), where they are stochastically excited by turbulent convective motions alone. It is implied that our code can be used to study the magnetic cycle dependence of the Rossby modes (or inertial modes in general) in the future.…”
Section: Non-axisymmetric Flowscontrasting
confidence: 60%
See 1 more Smart Citation
“…We can clearly see the existence of the equatorial Rossby modes as represented by a clear power ridge along the expected dispersion relations (red points) for 3 ≤ m ≤ 12. In our simulation, these Rossby modes are excited both by the non-axisymmetric random fluctuations in the Λ-effect and by the non-axisymmetric Lorentz-force; this is different from the rotating convection simulation of Bekki et al (2022b), where they are stochastically excited by turbulent convective motions alone. It is implied that our code can be used to study the magnetic cycle dependence of the Rossby modes (or inertial modes in general) in the future.…”
Section: Non-axisymmetric Flowscontrasting
confidence: 60%
“…In order to avoid the singularities in a spherical coordinate at the poles, we used the Yin-Yang grid (Kageyama & Sato 2004). For more details about the implementation of the Yin-Yang grid, refer Bekki et al (2022b).…”
Section: Numerical Schemementioning
confidence: 99%
“…Therefore, an accurate theoretical estimation of tidal dissipation is needed to interpret the orbital decay rate of the planet/accelerating spin of star. In the WASP-12 system, non-linear wave breaking of gravity waves (restored by buoyancy) in the radiative central portions of the host star is believed to be responsible for the inward spiralling of the planet (Chernov et al, 2017;Weinberg et al, 2017;Barker, 2020). In other systems where this mechanism probably cannot apply, tidal dissipation of inertial waves (restored by the Coriolis acceleration) in stellar convective envelopes could be another avenue to explain any inferred orbital decay, as in the KELT-1 Hot Jupiter/brown dwarf system (Maciejewski et al, 2022) or for the Hot Jupiter Kepler-1658b (Vissapragada et al, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…We fixed the Ekman number E = ν/(ΩR 2 ) to 10 −5 (e.g. Bekki et al, 2022) for an envelope as thick as the core (α = 0.5), where R is the outer radius. The nonlinear self-interaction of inertial waves along their shear layers triggers cylindrical differ-3 These can be shown to be small in our problem (Astoul & Barker, 2022), but they can lead to unrealistic evolution of the total angular momentum in a spherical model, as observed in Favier et al (2014) and demonstrated in Astoul & Barker (2022).…”
Section: Introductionmentioning
confidence: 99%
“…The same analysis method as § 3.2 is used for the Fourier transform in time and longitude. Note, however, that unlike the rotating convection simulation of Bekki et al (2022a), Rossby modes are excited by the non-axisymmetric random fluctuations in the Λ-effect and by the non-axisymmetric Lorentz-force in our non-convecting model. For comparison, we also compute the same power spectrum for the hydrodynamic (non-magnetic) simulation data, in which the non-axisymmetric flows are purely driven by the random fluctuations in the Λ-effect.…”
Section: Equatorial Rossby (R Modes)mentioning
confidence: 72%